CD83 expression induced by CpG-DNA stimulation in a macrophage cell line RAW 264.7 - Park, Min Chul (Korean Society for Biochemistry and Molecular Biology, 2013)
CpG-DNA has various immunomodulatory effects in dendritic cells, B cells, and macrophages. While induction of cytokines by CpG-DNA has been well documented in macrophages, the expression of costimulatory molecules in CpG-DNA treated macrophages has not yet been defined. Therefore, we investigated the effects of CpG-DNA on the expression of costimulatory molecules in RAW 264.7 cells. The surface expression of CD80 was slightly increased and CD83 expression was significantly increased in response to CpG-DNA. However, the expression of CD86 and MHC class II was not changed. As expression of CD83 mRNA was also increased by CpG-DNA, CD83 expression is regulated at a transcriptional level. To understand the contribution of signaling pathways to CD83 induction, we used pathway specific inhibitors. The NF-κB inhibitor significantly reduced surface expression of CD83 as well as phagocytic activity of RAW 264.7 cells. Therefore, CD83 expression may contribute to the immunostimulatory effects of CpG-DNA in macrophage cells. [BMB Reports 2013; 46(9): 448-453]